2023
DOI: 10.56632/bct.2023.2101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music on Communication Ability: A Case of Vocabularies

Abstract: Vocabulary growth predicts communication ability and communication without vocabulary is impossible. The study was done among 50 EFL learners to examine the effect of music-based instruction on their vocabulary retention and attitudes. They were divided into experimental and control groups. First, a pre-test was conducted to fulfill the homogeneity assumption. Then, the photo dictionary part of the “English for Schools Prospect 1” book was set to music and the experimental group underwent music-based practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…This study is also in line with several studies which confirm the negative correlation between language CA and succeeding in learning a foreign language (e.g., Horwitz, 2010;Trang et al, 2012). Moreover, Boustani and Al Abdwani (2023) demonstrated the effect of positive feelings on learning and communication through the use of music in the classroom.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study is also in line with several studies which confirm the negative correlation between language CA and succeeding in learning a foreign language (e.g., Horwitz, 2010;Trang et al, 2012). Moreover, Boustani and Al Abdwani (2023) demonstrated the effect of positive feelings on learning and communication through the use of music in the classroom.…”
Section: Discussionsupporting
confidence: 91%
“…Acquiring the ability to communicate effectively is essential for L2 learners as, through this ability, they can exchange their thoughts and emotions (Boudreau et al, 2018); moreover, Cheng and Xu (2022) state the importance of effective communication in affecting the audience to achieve one's desired goal or to succeed. Studies have shown that many factors can affect communication, e.g., learners' vocabulary knowledge (Boustani & Al Abdwani, 2023) or EFL teaching materials (Harsono, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation